M11 The use of asthma care bundle proformas can improve quality of care in acute asthma admissions. (15th November 2017) - Pace-Bardon, M; Bilocca, D; Jackson, K; Bradding, P; Green, RH
Abstract : Introduction: Despite the introduction of dedicated asthma services and targeted therapies, asthma exacerbations remain a common cause of hospital admission with significant utilisation of health care resources. Aim: To determine whether asthma care bundle proformas contribute to improved quality of care in adult patients admitted to Glenfield Hospital with an asthma exacerbation Method: Data collected at Glenfield hospital as part of the national BTS Adult Asthma audit in 2011 and 2012, prior to the introduction of asthma care bundles, was compared to data collected using a similar methodology in 2016, when both admission and discharge bundles had been introduced. The Results were analysed using Chi-squared Testing. Results: Asthma Care bundles were used in 64.4% of asthma admissions audited in 2016. When compared to 2011 and 2012, prior to the introduction of care bundles, there was a statistically significant increase in the proportion of patients having a documented peak flow on admission from 73.1% in 2011/2% to 94.4% in 2016 (p=0.001). There was also an improvement in the frequency of inhaler technique assessment on discharge with an increase from 52.5% in 2011/2% to 73.8% in 2016 (p=0.012). Of those patients given a hospital follow-up, more patients were seen within 4 weeks, with a statistically significant rise from 32.0% in 2011/2% to 70.6% in 2016 (p=0.001). Over the same period, the percentage of admitted patients who had been admitted with asthma in the previous month, which approximates to the 1 month re-admission rate, fell from 10.0% to 4.4%. There were also improvements in the use of written personal asthma plans with an increase from 60.9% to 69.8%, however this did not reach statistical significance (p=0.053). Other outcomes which were not affected by the introduction of bundles included adherence review and assessment of triggering and exacerbating factors. Discussion: Apart from the direct use of the bundle itself in a proportion of patients, the introduction of a standardised asthma bundle proforma on admission and discharge may have also served an indirect role in reinforcing education and awareness of BTS/SIGN asthma guidelines. Several positive outcomes were noted, however other important outcomes were not affected.